2017
DOI: 10.1161/circheartfailure.117.003863
|View full text |Cite
|
Sign up to set email alerts
|

Early Right Ventricular Assist Device Use in Patients Undergoing Continuous-Flow Left Ventricular Assist Device Implantation

Abstract: Background To investigate pre-implant risk factors associated with early right ventricular assist device (RVAD) use in patients undergoing continuous-flow left ventricular assist device (CF-LVAD) surgery. Methods and Results Patients in the INTERMACS registry who underwent primary CF-LVAD surgery were examined for concurrent or subsequent RVAD implantation within 14 days of LVAD. Risk factors for RVAD implantation and the combined endpoint of RVAD or death within 14 days of LVAD were assessed with stepwise l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 27 publications
1
58
0
1
Order By: Relevance
“…Notably, previous work has shown that clinical variables reflecting hemodynamic instability and end-organ dysfunction (and thereby severity of RV dysfunction) drive much of the ability of scores to predict RVF. (34,35) The incidence of RVF in our study was lower than that reported in some other published studies, (18,19,27) but was similar to the recently published Euromacs study. (22) The wide variation in the reported incidence of RVF in previous studies has been attributed to heterogeneities in RVF definitions.…”
Section: Discussionsupporting
confidence: 90%
“…Notably, previous work has shown that clinical variables reflecting hemodynamic instability and end-organ dysfunction (and thereby severity of RV dysfunction) drive much of the ability of scores to predict RVF. (34,35) The incidence of RVF in our study was lower than that reported in some other published studies, (18,19,27) but was similar to the recently published Euromacs study. (22) The wide variation in the reported incidence of RVF in previous studies has been attributed to heterogeneities in RVF definitions.…”
Section: Discussionsupporting
confidence: 90%
“…The clinical settings in which RVAD therapy are most commonly employed include acute myocardial infarction, pulmonary embolism, pulmonary hypertension, myocarditis, post-cardiotomy shock, cardiac transplantation, and LVAD implantation. As the frequency of LVAD use continues to rise, this last scenario is becoming increasingly common as nearly half of all CHF patients show right heart failure after LVAD implantation and 4% require RV support within the first two weeks post-operation [27,28]. Because RV complications after LVAD surgery are both relatively frequent and highly significant in terms of morbidity and mortality, the means to provide right ventricular mechanical support is now considered an essential capability in medical centers where LVAD therapy is performed [18,28].…”
Section: The History Of Cardiac Assist Devicesmentioning
confidence: 99%
“…As the frequency of LVAD use continues to rise, this last scenario is becoming increasingly common as nearly half of all CHF patients show right heart failure after LVAD implantation and 4% require RV support within the first two weeks post-operation [27,28]. Because RV complications after LVAD surgery are both relatively frequent and highly significant in terms of morbidity and mortality, the means to provide right ventricular mechanical support is now considered an essential capability in medical centers where LVAD therapy is performed [18,28]. Today, some RVADs like SynCardia (SynCardia Systems, Tucson, AZ, USA) serve as BTT while some others like Impella RP (AbioMed, Danvers, MA, USA), TandemHeart (CardiacAssist, Pittsburgh, PA, USA), and CentriMag RVAD (Thoratec) serve as peri-operative bridges to mechanical support [17,29].…”
Section: The History Of Cardiac Assist Devicesmentioning
confidence: 99%
“…1 We agree that the right ventricle dysfunction associated with LVAD implantation poses a frequent and serious challenge in both the early and late stages of LVAD support. 2,3 The role of the tricuspid valve and preservation of the structure of the tricuspid valve annulus seems to play a role in late right ventricular failure after LVAD implantation as patients who suffer failure of a tricuspid valve repair have higher incidence of late right ventricular failure after LVAD implant. 4 Tricuspid valve regurgitation is a known complication of transvenous pacing by several potential mechanisms, and we agree with you that theoretically a leadless pacing system could reduce tricuspid valve regurgitation and potentially alter outcomes in LVAD patients, although this has not been substantiated by any published literature.…”
Section: Reply: Advantage Of Leadless Pacemaker Over the Conventionalmentioning
confidence: 99%